Simulation Framework for Wind Energy Attributes with WAsP - Yilmaz, Unal; Balo, Figen; Sua, Lutfu S. (Elsevier B.V., 2019)
Electricity generation from wind energy has the potential to contribute positively to energy production in an economic way as a result of technological developments. Wind farms, where wind energy is converted into electrical energy, are preferred because there is no other expense except for initial costs and maintenance costs and there is no raw material cost. The wind turbine converts the available air flow into electrical energy. Since the plants that generate electricity by wind power do not cover much space and do not emit harmful gas to the atmosphere, they have no negative effect on the atmosphere. Therefore, it also benefits the protection of the ecological balance. Since the parts of the wind farms can be used as recycling during their maintenance, they do not have any waste and have no significant impact on the environment which is harmful to the environment. In this study, potential of a specific province in terms of wind energy and capability of electrical energy that can be obtained from wind energy potential to meet energy demand in the province has been investigated For this purpose; With the data obtained from the General Directorate of State Meteorology, the wind energy potential was analyzed for this province using the WASP (Wind Atlas Analysis and Application Program) simulation program. In the simulation program, hourly wind speeds and wind data obtained from the latitude and longitude of the province through meteorological stations for the province were loaded as input to the program. As a result, wind power that can support electrical energy and turbine systems that can activate this potential have been identified. This study supported renewable energy power generation of a specific location and hence the aim is to create awareness about contributions than can economically provide energy to the whole country. © 2019 The Authors. Published by Elsevier B.V.
3rd World Conference on Technology, Innovation and Entrepreneurship, WOCTINE 2019 -- 21 June 2019 through 23 June 2019 -- Istanbul -- 141488
Keywords: Renewable Energy; Simulation; Sustainable energy; Wind energy; Wind farm feasibility